Buccoadhesive Drug Delivery - A Potential Route of - jonwal, nitin (International Journal of Pharmaceutical & Biological Archive, 2010)
Within the oral mucosal cavity, the buccal region offers an attractive route of administration for systemic drug delivery. The mucosa has a rich blood supply and is permeable to many pharmacologically active agents. The main obstacles that drugs meet when administered via the buccal route derive from the limited absorption area and the barrier properties of the mucosa. The effective physiological removal mechanisms of the oral cavity that take the formulation away from the absorption site are the other obstacles that have to be considered. The strategies studied to overcome such obstacles include the employment of new materials that, possibly, combine mucoadhesive and penetration enhancer properties and the design of innovative drug delivery systems which, besides improving patient compliance, favor a more intimate contact of the drug with the absorption mucosa. The objective of this article is to review buccal drug delivery by discussing the structure and environment of the oral mucosa and highlighting the experimental methods used in the assessment of buccal drug permeation and absorption. The review also assesses the current status of buccal permeation enhancers as well as buccal drug delivery systems.